Haematological, clinical–chemical and immunological consequences of feeding Fusarium toxin contaminated diets to early lactating dairy cows - Dänicke, Sven (Mycotoxin Res, 2016)
Dairy cows experience a negative energy balance at the onset of lactation which results in an enhanced vulnerability for infectious diseases. Any dietary imbalances, including Fusarium toxin contamination, might therefore exacerbate this situation. The aim of the present investigations was to study the effects of increasing dietary concentrations of deoxynivalenol (DON) and zearalenone (ZEN) on clinical-chemical, haematological and immunological traits up to week 14 of lactation. For this purpose, ten cows each were assigned to a control group (CON; 0.02 mg ZEN and 0.06 mg DON per kg diet at 88 % DM), toxin level 1 (TOX-1; 0.29 mg ZEN and 2.31 mg DON per kg diet at 88 % DM) and toxin level 2 (TOX-2; 0.58 mg ZEN and 4.61 mg DON per kg diet at 88 % DM). The measured values of most parameters were affected by parturition but only a few of them were further modified by dietary treatment. For example, the time-dependent decrease in haemoglobin concentration, haematocrit and erythrocyte counts occurred at a significantly higher level for group TOX-2 while a serum glucose increase was missing in this group. Proportions of CD4+ and CD8+ cells decreased significantly over time solely in group TOX-2 while the CD4+/CD8+ ratio remained uninfluenced. Ability of granulocytes to mount an oxidative burst tended to increase at the end of the study in groups TOX-1 and TOX-2 while the opposite was observed in group CON. The results of this time-limited study indicate that feeding of Fusarium-toxin contaminated diets in early lactation affects health related parameters without compromising milking performance. However, long-term consequences of the observed effects on health need to be addressed in further studies.